2016
DOI: 10.1021/acs.nanolett.6b01061
|View full text |Cite
|
Sign up to set email alerts
|

Dark High Density Dipolar Liquid of Excitons

Abstract: The possible phases and the nanoscale particle correlations of two-dimensional interacting dipolar particles is a long-sought problem in many-body physics. Here we observe a spontaneous condensation of trapped two-dimensional dipolar excitons with internal spin degrees of freedom from an interacting gas into a high density, closely packed liquid state made mostly of dark dipoles. Another phase transition, into a bright, highly repulsive plasma, is observed at even higher excitation powers. The dark liquid stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 31 publications
(76 reference statements)
8
61
1
Order By: Relevance
“…We conclude that the Z line is not due to recombination of the liquid carriers, as we postulated in [12], but rather -recombination in the presence of the liquid. It is plausible to assume that it is due to recombination of carriers in the NW and WW which have not relaxed into the condensate with opposite charge carriers from the condensate.Evidence for the non-radiative nature of the dipolar exciton liquid was recently reported in [11]. It was suggested that the excitons condense in a "dark" state, consisting of electrons and holes in parallel spin configuration that cannot couple to light.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that the Z line is not due to recombination of the liquid carriers, as we postulated in [12], but rather -recombination in the presence of the liquid. It is plausible to assume that it is due to recombination of carriers in the NW and WW which have not relaxed into the condensate with opposite charge carriers from the condensate.Evidence for the non-radiative nature of the dipolar exciton liquid was recently reported in [11]. It was suggested that the excitons condense in a "dark" state, consisting of electrons and holes in parallel spin configuration that cannot couple to light.…”
mentioning
confidence: 99%
“…Their relatively light mass, which is smaller than that of a free electron, implies that the necessary conditions for achieving quantum degeneracy can occur already at cryogenic temperatures, and their strong dipole-dipole interaction may give rise to formation of ordered phases. Extensive attempts have been made over the past two decades to observe these phases and to determine the phase diagram of this system [3][4][5][6][7][8][9][10][11][12].In recent years there are mounting evidences for a phase transition that occurs at low temperatures in this system, yet its nature and thermodynamics remain open questions.Many of the studies are performed in a trap geometry, which confines the excitons to a narrow region around the illuminated spot [13,14], and evidences for condensation are found through photoluminescence (PL) anomalies: The appearance of spontaneous coherence [7], onset of non-radiative recombination ("PL darkening") [9] and large blueshift of the PL energy [10,11]. An alternative approach to study this phase transition uses an open geometry, where photo-excited carriers are free to move away from the illumination spot, and their diffusion is limited only by the mesa boundary.…”
mentioning
confidence: 99%
“…Unambiguous optical evidences for Bose-Einstein condensation are bound to the density regime where dark and bright components coexist coherently [5]. The expected darkening [6][7][8][9][10] of the exciton gas upon cooling has been recently seen. Macroscopic spatial coherence of the bright component has also been revealed [7,10], in this way providing the most unambiguous evidence for the coexistence of dark and bright exciton condensates.…”
mentioning
confidence: 98%
“…The transition to a BEC is supposed to occur below a certain critical temperature T c , which is in a first approximation proportional to n IX /m*, with n IX the exciton density and m* the effective mass of the IXs [24] . The critical temperature for condensation in dipolar exciton systems can be estimated to be in the order of T c ≈ 1K [25] .Dipolar exciton systems realized in GaAs and InGaAs based CQWs exhibit a variety of exciting experimental signatures [8,[26][27][28][29][30] . Nevertheless, an unambiguous proof for BEC and long range coherence is challenging [27,[31][32][33] .…”
mentioning
confidence: 99%
“…Dipolar exciton systems realized in GaAs and InGaAs based CQWs exhibit a variety of exciting experimental signatures [8,[26][27][28][29][30] . Nevertheless, an unambiguous proof for BEC and long range coherence is challenging [27,[31][32][33] .…”
mentioning
confidence: 99%